THE HUMAN TEAM N THE HEALTHCARE ENVIRONMENT - Cobos Aranda, M; Marin Hernandez, Ma J (Cuestiones de Fisioterapia, 2004)
Work teams in business have a long tradition if we compare them with teams within the field of health. In the area of health the clearest example would be the surgical team, where you can see a group of people with different training pointed to the same aim. Some aspects of work teams can be found in primary health care levels in some places of Spain. These examples are more usual in public health. The current private health development in Spain doesn't contemplate these elements yet. Throughout this article we will present the main elements which are involved in the dynamics and environment of work teams.